A new species and a new record of the genus Rhamphothrips Karny (Thysanoptera, Thripidae) from the Western Ghats, India - Sujith, K.m.; Rachana, R.r.; Hegde, J.n.; Vanitha, K. (Zootaxa, 2025)
Rhamphothrips laterocurvidentatus sp. nov., is described based on specimens collected from the leaves of Streblus sp. Rhamphothrips tenuirostris (Karny), originally described from Indonesia, is reported here as a new record for India. An updated key to the nine Rhamphothrips species recorded from India is also provided.